In Vitro Evaluation of Feed Quality of Fermented Tithonia diversifolia with Lactobacillus bulgaricus and Persea americana miller Leaves as Forages for Goat - Pazla, R.; Jamarun, N.; Arief; Elihasridas; Yanti, G.; Putri, E. M. (Tropical Animal Science Journal, 2023)
Fermented Tithonia diversifolia and Persea americana miller or avocado leaves as local alternative forages for goats are potential as protein, mineral, and energy sources. Therefore, this study aimed to evaluate the effect of fermented Tithonia diversifolia (FTD) and avocado leaves (AL) combination on in vitro nutrient digestibility, rumen fluid characteristics, and methane production. This study consisted of 3 trials. Trial 1 evaluated FTD’s nutrient content with Lactobacillus bulgaricus with different durations of fermentation arranged in a completely randomized design consisting of five treatments and four replications. The treatments were T. diversifolia without fermentation and fermentation of T. diversifolia for 2, 3, 4, and 5 days. Trial 2 was in vitro evaluation on different days of fermented T. diversifolia in a completely randomized design consisting of four treatments and four replications. Trial 3 was in vitro evaluation of FTD for 5 days and AL combination, which consisted of four combinations. FTDAL1 = 20% FTD+80% AL; FTDAL2 = 40% FTD+60% AL; FTDAL3 = 60% FTD+40% AL; and FTDAL4 = 80% FTD+20% AL. Experimental diets were incubated using Tilley and Terry method. Fermentation of T. diversifolia using L. bulgaricus significantly increased nutrient components (p<0.01), nutrient digestibility (p<0.01), and rumen fluid characteristics (p<0.05). In vitro evaluation of FTD and AL combination significantly increased nutrient digestibility, total volatile fatty acid, ammonia concentration, total gas production, and methane production (p<0.05), but insignificantly affected pH rumen fluid. It is concluded that the combination of 80% fermented T. diversifolia and 20% avocado leaves has the potential to increase dry matter, organic matter, crude protein, cellulose digestibility, and rumen fluid characteristics, but it is not optimum to decrease total gas and methane gas production.